Cannabidiol use among elite-level Canadian athletes: the pursuit of improved sleep, pain relief, and enhanced recovery - Sesbreno, E.; Karam, D.; Drager, K.; Boegman, S.; Duncan, L.; Jensen, D.; Churchward-Venne, T. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2025)
Cannabidiol (CBD) is a non-psychoactive cannabinoid found in the cannabis plant. The purported physiological and psychological effects of CBD may benefit athletes` ability to train and recover. Cannabis, cannabis products, tetrahydrocannabinol (THC) and synthetic cannabinoids mimicking the effects of THC have been banned by the World Anti-Doping Agency while CBD remains on the list of exceptions. Lack of clarity in the manufacturing practices of commercially available CBD-containing products may pose a risk of inadvertent doping due to the possible presence of other banned cannabinoids. The prevalence, rationale, and perceived benefits of CBD use in elite Canadian athletes has not been explored. The primary aim of this study was to characterize the point-prevalence and rationale for CBD use by tier 3 to 5 level athletes in Canada. Secondary aims were to identify the (1) expected and perceived benefits, (2) barriers or deterrents to, (3) and the sources of information that influence the use of CBD, as well as (4) to describe the reported methods of CBD use. Using a cross-sectional design, Canadian athletes from Olympic and Paralympic sport programs were invited to complete a self-administered and anonymous online survey between October 2021 and June 2023 to gather information on CBD use. Eighty tier 3 to 5 level Canadian athletes completed the survey. Thirty-seven percent of the athletes had used CBD, with 30% of users reporting active use. Oral tincture/oil was the most commonly used (31%) form of CBD. Most CBD users (55%) relied on "trial and error" to find their optimal dose. The most reported reason for discontinuing CBD (52%) was fear of an unintentional anti-doping violation secondary to product contamination with THC and/or other banned cannabinoids. Among CBD users, 96% agreed that CBD is safe; improves sleep (93%) and relaxation (90%); reduces pain from training (77%); enhances physical (73%) and mental (70%) recovery after training or competition; reduces pain from competition (70%) and improves symptoms of anxiety (60%) and depression (54%). Our findings indicate that athletes use CBD for multiple reasons. This information may help to inform future research on the effects of using CBD by athletes and the risk of inadvertent doping from using CBD-containing products marketed to athletes.